Design and Implementation of an Indoor and Outdoor Air Quality Measurement Device for the Detection and Monitoring of Gases with Hazardous Health Effects - Johnathan Gabriel Caselles Nuñez; Oscar Alejandro Contreras Negrette; Kelvin de Jesús Beleño Sáenz; Carlos Gabriel Díaz Sáenz (Engineering Proceedings, 2025)
This paper presents a detailed step-by-step design and construction of an indoor and outdoor air quality monitoring device, composed of electronic sensors capable of measuring gases such as Carbon Monoxide (CO), Nitrogen Dioxide (NO2), Ozone (O3), in addition to measuring temperature and humidity, as well as concentrations of PM2.5 and PM10 particulate matter suspended in the environment. The device features the ESP32 microprocessor board that integrates IoT wireless connectivity via Wi-Fi, which allows for longer processing time and wireless communication. To evaluate the accuracy of the Q-air device, measurements were taken at strategic sites in the city of Barranquilla, which were compared with data from stationary monitoring stations in the city, the results obtained by Q-Air showed a margin of error less than 1.6%, demonstrating accuracy and efficiency.